6,6-[Ethylenebis(sulfanediyl)]-2-(2-methoxyethyl)-1,2,3,4,5,6-hexahydro-1,5-methano-1H-azocino[4,3-b]indol-3-one - Tercan, Baris; Yüksel, Fatma; Patir, Sueleyman; Hokelek, Tuncer (Int Union Crystallography, 2010)
The title compound, C19H22N2O2S2, consists of a tetracyclic ring system containing an azocine skeleton with methoxyethyl and dithiolane groups as substituents. The benzene and five-membered N-heterocyclic rings are nearly coplanar, making a dihedral angle of 0.81 (12)degrees. The dithiolane ring adopts an envelope conformation. Intermolecular N-H center dot center dot center dot O hydrogen-bonding and weak C-H center dot center dot center dot pi interactions are present in the crystal structure.